Role of Components of the Insulin-like Growth Factor System in the Early Stages of Ovarian Follicular Persistence in Cattle. Issue 2 (August 2017) - Rodríguez, F.M.; Gareis, N.C.; Hein, G.J.; Salvetti, N.R.; Amweg, A.N.; Huber, E.; Stassi, A.F.; Ortega, H.H.; Rey, F.
Summary: Cystic ovarian disease (COD) is one of the main causes of infertility in dairy cattle. It has been postulated that the insulin-like growth factor (IGF) system may contribute to follicular persistence and development of COD. The initiation of the IGF response is a result of interactions between IGF-binding proteins (IGFBPs) and IGFBP proteases, mainly pregnancy-associated plasma protein A (PAPP-A). IGFBPs bind IGFs with high affinity and consequently regulate their access to IGF receptors (IGFRs). The aim of this research was to determine variations in components of the IGF system in the ovaries of cows with persistent follicles induced by long-term administration of progesterone. Proteins of the IGF system were evaluated at 0 (expected day of ovulation), 5, 10 and 15 days of follicular persistence to determine whether the changes occur early in the development of COD. The concentrations of IGF1 and IGFBP4 in follicular fluid were similar in all groups with follicular persistence and in control antral follicles. IGFR1 and IGFBP4 expression in situ were higher in granulose cells in persistent follicles than in control follicles. No differences were found in PAPP-A concentration within follicular fluid in persistent follicles relative to control antral follicles. These data support the hypothesis that the IGF system is altered in the initial stages of development of follicular persistence and has a determinant role in ovarian function in cattle. Graphical abstract: